THE EFFECTS OF SUBTHALAMIC AND PALLIDAL DEEP BRAIN STIMULATION ON POSTURAL RESPONSES IN PATIENTS WITH PARKINSON'S DISEASE - St George, Rebecca J (2012)
OBJECT: The effect of Deep Brain Stimulation (DBS) for Parkinson's disease (PD) on balance is unclear. The goal of this study was to investigate how automatic postural responses were affected in subjects randomized to either the Subthalamic Nucleus (STN) or the Globus Pallidus interna (GPi) surgery. METHODS: We tested 24 PD subjects who underwent bilateral DBS, 9 PD control subjects without DBS, and 17 age-matched control subjects. Electrode placement site was randomized and blinded to PD subjects and experimenters. Kinematic, kinetic and electromyographic recordings of postural responses to backward disequilibrium via forward translations of the standing surface were recorded in the week prior to surgery while off (OFF) and on antiparkinsonian medication (ON) and then 6 months after surgery in four conditions: off medication with DBS switched off (OFF/OFF), off medication with DBS on (DBS), on medication with DBS off (DOPA), and both medication and DBS on (DBS+DOPA). Stability of the automatic postural response (APR stability) was measured as the difference between the displacement of the center of pressure and the projected location of the center of body mass. RESULTS: PD subjects had worse APR stability than control subjects. Turning the DBS on at either site improved APR stability compared to the postoperative off condition by lengthening the tibialis response, whereas medication did not show an appreciable effect. The STN group had worse APR stability in their best functional state (DBS+DOPA) six months after the DBS procedure compared to their best functional state (ON levodopa) before the DBS procedure. In contrast, the GPi group and the PD control group showed no change over 6 months. APR stability impairment in the STN group was associated with smaller tibialis response amplitudes, but no change in response latency or co-activation with gastrocnemius. CONCLUSIONS: Turning the DBS current on improved APR stability for both STN and GPi sites. However, there was a detrimental DBS procedural effect for the STN group and this effect was greater than the benefit of the stimulating current, making overall APR stability functionally worse after surgery for the STN group.